A sourcebook on the compliance review function of ADB accountability mechanism.
It explains the compliance review function of ADB Accountability Mechanism, which is the grievance redress platform of last resort for people and communities who may be unduly, adversely,or potentially affected by ADB assisted projects. The sourcebook explains the roles of and information expected from different stakeholders at every stage of the compliance review process.